Very Ordinary Communists: The Life of Ivan and Lesley Schermbrucker - Kirkaldy, Alan (South African Historical Journal, 2017)
This paper sets out to portray how very ordinary people could be drawn into the struggle and play significant roles based on stances more rooted in common decency and morality than in the writings of Marx and Lenin. Ivan Schermbrucker was a member of the Central Committee of the SACP. It was he who recruited Walter Sisulu (among others) into membership of the Party. Detained under the 90 day legislation, he was tortured, and was the subject of an infamous appeal court decision. This established a precedent for limiting the rights of courts to call detainees to testify on the conditions under which they were being held. He was subsequently tried and imprisoned under the Suppression of Communism Act. To all intents and purposes, his wife, Lesley, was a 'typical' middle-class South African housewife. She loved entertaining, swimming, playing tennis and going to restaurants, movies and plays. What was less apparent was that she, too, was an ardent communist and served on the Central Committee. She would also be jailed for her refusal to testify against Bram Fischer and having assisted in hiding him during his 'Red Pimpernel' period. Neither Ivan nor Lesley was a theoretician. Neither had a university education. Both came from economically disadvantaged backgrounds. Their commitment to communism, and to the SACP, grew directly out of the firm conviction that South African society was deeply dysfunctional and that the only fair solution lay in the achievement of a classless, non-racist, society.